The Natural Killer T (NKT) Cell Ligand α-Galactosylceramide Demonstrates Its Immunopotentiating Effect by Inducing Interleukin (IL)-12 Production by Dendritic Cells and IL-12 Receptor Expression on NKT Cells - Kitamura, Hidemitsu (The Rockefeller University Press, 1999)
The natural killer T (NKT) cell ligand α-galactosylceramide (α-GalCer) exhibits profound antitumor activities in vivo that resemble interleukin (IL)-12–mediated antitumor activities. Because of these similarities between the activities of α-GalCer and IL-12, we investigated the involvement of IL-12 in the activation of NKT cells by α-GalCer. We first established, using purified subsets of various lymphocyte populations, that α-GalCer selectively activates NKT cells for production of interferon (IFN)-γ. Production of IFN-γ by NKT cells in response to α-GalCer required IL-12 produced by dendritic cells (DCs) and direct contact between NKT cells and DCs through CD40/CD40 ligand interactions. Moreover, α-GalCer strongly induced the expression of IL-12 receptor on NKT cells from wild-type but not CD1(−/−) or Vα14(−/−) mice. This effect of α-GalCer required the production of IFN-γ by NKT cells and production of IL-12 by DCs. Finally, we showed that treatment of mice with suboptimal doses of α-GalCer together with suboptimal doses of IL-12 resulted in strongly enhanced natural killing activity and IFN-γ production. Collectively, these findings indicate an important role for DC-produced IL-12 in the activation of NKT cells by α-GalCer and suggest that NKT cells may be able to condition DCs for subsequent immune responses. Our results also suggest a novel approach for immunotherapy of cancer.